Contaminant dust suppression materials: A cost-effectiveness estimation methodology. (November 2016) - Inyang, Hilary I.; Bae, Sunyoung; Pando, Miguel A.
Abstract: Chemical dust suppressants generally require more than one application to exposed ground surfaces to maintain the soil wetness level required to reduce dust emissions under the combined action of wind, high ambient temperature, low relative humidity, and vehicular traffic. A quantitative methodology is herein formulated for estimation of the cost-effectiveness of dust suppression with chemical agents within a specified construction duration. This is applied to the 3 polymers: sodium carboxymethyl cellulose (CMC A), polyacrylamide (PAM B) and polyethylene oxide (PEO A) used on 2 base soils (sodium montmorillonite (Na-montmorillonite) and kaolinite (K)). Polymer aqueous concentrations ranging from 0.5 g/L to 10 g/L, with distilled water as control, were used to perform desiccation tests at 25 °C and 30% relative humidity. The results show that liquid loss kinetics alone which indicated CMC A at 8 g/L and 4 g/L aqueous concentrations for Na-montmorillonite during 891 h and kaolinite during 696 h, respectively, may not provide complete information on the potential cost-effectiveness of dust suppressants over multiple applications in the field. It identifies water and PAM B at <0.1 g/L as the cost effective for Na-montmorillonite with PEO A, water and PAM B at similarly low concentrations are the most cost effective for kaolinite.